2008
DOI: 10.1073/pnas.0801389105
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of the uncultured Termite Group 1 bacteria in a single host protist cell

Abstract: Termites harbor a symbiotic gut microbial community that is responsible for their ability to thrive on recalcitrant plant matter. The community comprises diverse microorganisms, most of which are as yet uncultivable; the detailed symbiotic mechanism remains unclear. Here, we present the first complete genome sequence of a termite gut symbiont-an uncultured bacterium named Rs-D17 belonging to the candidate phylum Termite Group 1 (TG1). TG1 is a dominant group in termite guts, found as intracellular symbionts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
265
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(271 citation statements)
references
References 39 publications
6
265
0
Order By: Relevance
“…The endosymbionts of termite-gut cellulolytic protists in the genus Pseudotrichonympha and Trichonympha have smaller genomes (1.1 Mb in each case) rich in pseudogenes, and thus their ongoing genome erosion is suggested (20,21). In contrast, the estimated genome size of the endosymbiont of Eucomonympha does not look severely reduced.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The endosymbionts of termite-gut cellulolytic protists in the genus Pseudotrichonympha and Trichonympha have smaller genomes (1.1 Mb in each case) rich in pseudogenes, and thus their ongoing genome erosion is suggested (20,21). In contrast, the estimated genome size of the endosymbiont of Eucomonympha does not look severely reduced.…”
Section: Discussionmentioning
confidence: 77%
“…It is possible that, after the two lineages separated, they acquired the endosymbionts independently or that the endosymbiont of one lineage was replaced by another. In either case, the endosymbionts of both lineages seem to share many functions, such as nitrogen fixation, utilization of urea and ammonia, glycogen metabolism, and H 2 consumption, although H 2 is not used for reductive acetogenesis in the endosymbiont of Pseudotrichonympha, in addition to upgrading nitrogenous nutrients and the utilization of sugars, which are also common to the genome-sequenced endosymbiont of Trichonympha that belongs to the phylum Elusimicrobia (21). These common features suggest that different bacterial species have convergently established the similar intracellular niches of the cellulolytic protists and that these functions are important for the establishment of the endosymbiotic relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of any nitrogenase genes from 'Endomicrobium trichonymphae' (Hongoh et al, 2008a)-the closest relative of the second symbiont of D. arta -and the apparent absence of 'Endomicrobia' from S. tabogae strongly suggest that both the Arma-1 (anfH) and the Bact-1a (nifH) paralogs stem from 'A. devescovinae' and the closely related symbiont of S. tabogae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, spirochetes and Bacteroidales bacteria are attached to its cell surface (Hongoh et al, 2007b). The complete genome sequence analysis of phylotype Rs-D17 suggested that the endosymbionts contribute to the host protists and termites by the synthesis of amino acids and cofactors, which are deficient in the ingested wood materials (Hongoh et al, 2008a). Likewise, termite gut protists generally harbor diverse intracellular and/or extracellular symbiotic prokaryotes comprising members of the orders Spirochaetales, Bacteroidales, 'Endomicrobiales', Desulfovibrionales, Actinomycetales and Methanobacteriales (Hongoh and Ohkuma, 2011;Desai and Brune, 2012;Strassert et al, 2012).…”
Section: Introductionmentioning
confidence: 99%